Analysis of the causality between regional capital expenditure and local own-source revenue in Maluku province - Rumerung, Dientje; Oppier, Hermi; Ramly, Fahrudin; Tamtelahitu, Jopie; Matitaputty, Izaac Tonny (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Government initiatives to improve public services are critically necessary by taking into account the region’s entire potential. The regional government employs infrastructure development for public services by allocating funds in the form Regional Government Budget (RGB)) from the regional capital expenditure budgets. The infrastructure development allows the regional government to collect levies and taxes on to boost the Local Own-Source Revenue This study aims to investigate the causality between regional capital expenditure and Local Own-Source Revenue in 11 regencies / cities in Maluku province for a 10-year period (2011-2020). A quantitative method using a Granger causality approach was employed. The data was collected using a purposive sampling method from the Statistics Indonesia of Maluku and analysis with Multiple Linear Regression Method. The results show that there is a unidirectional relationship between the Local Own-Source Revenue and regional capital expenditure. However, there is no causal relationship between regional capital expenditure and Regional Original Income. These results indicate that capital expenditure does not indicate the funding source for Local Own-Source. The implication is that Local Own-SOurce has not been able to meet capital expenditure needs. Therefore, the ability of regional governments to optimize regional income sources through extensification and intensification of potential economic sources reduces regional governments' dependence on central government finance.